Survival of Staphylococcus aureus and Escherichia coli on Cotton Fabrics Treated with Extracts of Garad (Acacia nilotica - elsdeeg, yousra alamin; Abdel - Rahim, Awad M.; Idris, Fadl Elmoula A. (Gezira Journal of Engineering and Applied Sciences, 2018)
The transfer of pathogenic bacteria and other microorganisms among patients in hospitals is a growing concern. One of the critical aspects of bacterial transmission from a person (patient or a health care worker) to the environment and then to another person is the ability of the microorganism to survive on various common hospital materials, such as fabrics (Neely and Maley, 2000). Lee et al . (1969) found that Salmonella typhimurium, can remain viable and infectious on different fabrics, for relatively long periods of time. However, garments of health care workers are considered an important aspect of the environment that can easily become contaminated (Johnson, 1977). Fabrics treated with antimicrobial agents (antibiotics), are therefore, gaining popularity as a new promising area of research (Lee et al, 1969). However, antibiotic resistant strains of some bacteria such as the multi-resistant Staphylococcus aureus and vancomycin-resistant enterococci, have already been reported (Kim et al ., 1998; Neely and Maley, 2000). Plant extracts were suggested by many authors as an alternative to antibiotics. However, plant extracts were found effective against microorganisms since the beginning of the human civilization (Gilliver, 1947; Dix, 1974 and Zainal et al ., 1988). For inoculation, bacterial isolates of Escherichia coli and Staphylococcus aureus, which were obtained from the Food Microbiology Lab, University of Gezira, were grown in a nutrient agar medium (NA).